Judy Moody and Friends : Izzy Azumi, F.D.O. (Future Dog Owner) - McDonald, Megan; Madrid, Erwin (Somerville, Massachusetts : Candlewick Press, 2023)
"Fluffy dogs. Scruffy dogs. Pug-faced dogs. Ugh-faced dogs. Izzy Azumi has dogs on the brain! She already has a goldfish, a South American pink-toe tarantula, and two human best friends. But fish can't learn tricks, spiders can't cuddle, and Stink and Judy just aren't fuzzy enough. Will Izzy Azumi ever see her wish come true? All bets are off . . . until Izzy's father invites a certain sibling pair to help stage a surprise for their friend."--
Keywords: Dogs -- Juvenile fiction; Friendship -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Pets -- Juvenile fiction; Dogs -- Fiction; Friendship -- Fiction; Human-animal relationships -- Fiction; Pets -- Fiction; Juvenile fiction; Animal fiction